2006
DOI: 10.1128/ec.5.4.672-682.2006
|View full text |Cite
|
Sign up to set email alerts
|

High-Mobility-Group Box Nuclear Factors of Plasmodium falciparum

Abstract: In eukaryotes, the high-mobility-group (HMG) nuclear factors are highly conserved throughout evolution and are divided into three families, including HGMB, characterized by an HMG box domain. Some HMGB factors are DNA structure specific and preferentially interact with distorted DNA sequences, trigger DNA bending, and hence facilitate the binding of nucleoprotein complexes that in turn activate or repress transcription. In Plasmodium falciparum, two HMGB factors were predicted: PfHMGB1 and PfHMGB2. They are sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
64
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 67 publications
7
64
0
Order By: Relevance
“…While their classification as apicomplexan-specialized proteins may be surprising, inspection of their alignments expose variation between apicomplexan ribosomal proteins and those for other species (Supplemental File S1). Similar findings were observed for a group of chromatinrelated factors annotated as ''high mobility group'' proteins (Briquet et al 2006). Numerous gene duplication events have occurred in the Plasmodium and Toxoplasmatinae lineages, revealing potential differences in transcription regulation associated with each parasitic life cycle (Fig.…”
Section: Pan-apicomplexan Protein Familiessupporting
confidence: 67%
“…While their classification as apicomplexan-specialized proteins may be surprising, inspection of their alignments expose variation between apicomplexan ribosomal proteins and those for other species (Supplemental File S1). Similar findings were observed for a group of chromatinrelated factors annotated as ''high mobility group'' proteins (Briquet et al 2006). Numerous gene duplication events have occurred in the Plasmodium and Toxoplasmatinae lineages, revealing potential differences in transcription regulation associated with each parasitic life cycle (Fig.…”
Section: Pan-apicomplexan Protein Familiessupporting
confidence: 67%
“…Interestingly, these HMGB are differentially expressed. HMGB1 is expressed during the erythrocytic asexual cycle, whereas HMGB2 is slightly expressed at the schizont stage and highly expressed at the gametocyte stage (2,16).…”
mentioning
confidence: 99%
“…HMGB proteins also actively participate in chromatin remodeling by increasing nucleosome sliding and accessibility of the chromatin (17). The two Plasmodium falciparum HMGB proteins, HMGB1 (PFL0145c) and HMGB2 (MAL8P1.72), have the biochemical characteristics of the HMGB box family of transcriptional regulators (16). Interestingly, these HMGB are differentially expressed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Wu et al reported that HMGB1 expression was increased in AKI, and reportedly causes kidney damage through activation of the innate immune system 26 . In this context, HMGB1 triggers cellular signaling by binding to TLR4, which activates NFkB through a MyD88-dependent pathway and initiates the inflammatory response by releasing pro-inflammatory cytokines and chemokines 27 . Moreover, HMGB1 directly induces prothrombin expression on endothelial cells, which can contribute to the inflammatory response and exacerbate any renal impairment 12 .…”
Section: Discussionmentioning
confidence: 99%